Primary Amenorrhea Associated with Hyperprolactinemia in Polyglandular Autoimmune Syndrome Type II: A Case Report - Luiza Tizziotti Cottas; Maria de Fátima Borges; Lívia Prata Santos Oliveira; Ana Luísa Mantovani Resende; Meire Soares Ataíde; Elisabete Aparecida Mantovani Rodrigues Resende (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2018)
Abstract Polyglandular autoimmune syndrome type II (PGA-II) is a rare immunoendocrinopathy syndrome characterized by the occurrence of autoimmune Addison disease along with diabetes mellitus type 1 and/or autoimmune thyroid disease. Here, we report the case of a 23-year-old female with PGA-II who was followed up at the dermatology and endocrinology clinics of the Universidade Federal do Triângulo Mineiro, located in the state of Minas Gerais, Brazil. First, the patient presented diffuse skin hyperpigmentation, vitiligo; and in sequence, due to vomiting, appetite and weight loss, hypoglycemia, amenorrhea, and galactorrhea, the patient was then diagnosed with PGA-II. The patient also presented intense hyperprolactinemia due to primary hypothyroidism. The late diagnosis of PGA-II is frequent because the disorder is uncommon and has non-specific clinical manifestations. This report emphasizes the significance of a timely diagnosis and appropriate treatment to reduce morbidity and mortality associated with these diseases, especially Addison disease. The present study reports a rare case of a patient with PGA-II with primary amenorrhea associated with hyperprolactinemia.